In Ovo Vaccination Technology: An Alternative Approach to Post-Hatch Vaccination in Modern Poultry Operations - Wafaa A. Abd El-Ghany (Microbiology Research)
Poultry production systems are usually exposed to important infections that could be prevented by vaccination programs. Conventional methods of vaccination such as drinking water; spray, eye, or nose inoculation; and injection are usually given after hatching and have many disadvantages. Therefore, there is a great need for searching of alternative ways for vaccination process. In ovo vaccination technology is now regarded as an alternative approach to post-hatch vaccination in modern poultry operations. This technique is effective, fast, provides uniform vaccine dosing and delivery, is suitable for massive production, and reduces labor costs. Routine in ovo vaccination is applied during the late stage of embryonic development between days 17.5 and 19.25 of egg incubation. The best route of inoculation of the vaccine is in the amniotic fluid or in the embryo’s muscles, without causing any hatchability or chick quality losses. Accordingly, the inoculation site, the age of the embryos and breeders, presence of maternal antibodies, and the sanitation of equipment’s and the environment during the vaccination process affect the efficiency of the in ovo vaccination technique. In ovo vaccination technology is currently applied for vaccination against several economically important viral diseases such as Newcastle, infectious bursal disease, Marek’s disease, infectious laryngotracheitis, infectious bronchitis, avian influenza, and avian metapneumovirus. Moreover, vaccines used for prevention of mycoplasmosis and coccidiosis could be applied in ovo instead of in post-hatching application. It can be concluded that in ovo vaccination is a rapidly growing trend of vaccine technology, and it can replace post-hatching vaccination conventional methods.